Exposing Female Experiences: A Reading of Surjeet Kalsey’s Poetry - Kaur, Simran (Margins/Marges/Margini, 2025)
Understanding women's suffering by situating Surjeet Kalsey as a poet in the complex diaspora milieu of two distinct societies which is Indian (pertaining to Punjabi society) and Canadian. It is one of the pressing issues that are taken up as meaningful context in this paper. The aim of this article is to analyse the position of women as marginalised through various socio-cultural elements of the society as well as through their experiences. Kalsey’s poetry deals with the issues related to immigrant women on the Canadian soil. Her poems are testament to the imagery of the female experiences shown throughout her works. The poems of Surjeet Kalsey discuss the issues of immigrants, the situations and problems of women, culture, tradition, and human relations. She tries to bring forth or to centre stage the emotions, feelings, struggles of a woman which they experience and encounter in life. As a woman, Kalsey speaks for the women who are seen on margins and perhaps considered doubly marginalised. Being marginalised labels them as inferior, outcast, voiceless, powerless, suppressed both as female and immigrants. But the poet tries to challenge that by taking a stand as a "woman writer" who resists patriarchy and the oppression of women in Western society and culture through the selected poems of Surjeet Kalsey from Paunan Nal Guftagoo [Conversation with The Wind], Aurat Shabad te Shakti [Woman, Words & Strength], and Rom Rom Vich Jagdey Deewey [Body Illuminates].